Intervention to promote adolescents communication and engagement in diabetes clinic encounters: A pilot randomized controlled trial - Murphy, Maryanne; Coyne, Imelda; Hughes, Mary; Roche, Edna (My University, 2024)
Aim: To conduct a pilot randomized trial of an intervention to improve adolescent question-asking and provider education during paediatric diabetes visits. Methods: Adolescents aged 11 to 17 with type 1 diabetes and their parents were enrolled from two urban tertiary paediatric clinics. Adolescents were randomised to the intervention group or control group. Adolescent consultations were audio-recorded, their HbA1c level was recorded, and they completed surveys after three clinic appointments. The intervention group completed a question prompt list and watched a video on a tablet with their parents before meeting their doctor and completed a short evaluation after each visit. Results: Six consultant endocrinologists and ninety-nine adolescents and their parents participated. The intervention increased adolescents' question asking and provider education in diabetes encounters. Total patient question-asking across the 3 consultations and a higher baseline HbA1c at time one was significantly associated with HbA1c at time three. Conclusions: Question prompt lists and an educational video are useful tools to increase adolescents' question-asking and communication between adolescents and their providers. Practice implications: Interventions that encourage adolescents' question-asking in healthcare encounters may lead to more meaningful providers-adolescents' communication and tailored education. Interventions to improve professionals' listening, communication and educational skills are also required.
PUBLISHED
Keywords: Adolescent; Communication; Outpatient; Parents; Physicians; Type 1 diabetes mellitus; Creative Technologies; Digital Engagement; Adolescent Health; Health interventions and innovations ; Health outcomes;Health Informatics; Promotion of child centred research; TYPE 1 DIABETES; Therapeutic relationships and communication; question asking; Chronic Health Condition; Children